2018
DOI: 10.1007/s10570-018-1799-y
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated cellulose from N-methylmorpholine N-oxide solutions as a coating agent for paper materials

Abstract: The objective of the presented research was to determine the influence of cellulose coating, obtained from the cellulose solution in N-Methylmorpholine N-oxide (NMMO), on the structural and mechanical properties of paper. The effect of heating time of paper samples coated with cellulose dissolved in NMMO was also investigated. Depending on the heating time of the coating, a continuous or porous layer was obtained. Coating without any heating stage yielded a continuous cellulose layer of hydrophobic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…[ 60 ] The active N–O dipoles and the oxygen groups of NMMO can form hydrogen bonds with the anhydrous glucopyranose unit (AGU) of cellulose, leading to the disruption of the cellulose’s intermolecular hydrogen bonds, eventually establishing a strong complex by forming new hydrogen bonds in the homogeneous cellulose solution. [ 58,61 ] The commercialized Lyocell fibers spun from NMMO/H 2 O solution exhibit good mechanical properties up to 5.4 cN dtex −1 . [ 62 ] Nevertheless, Lyocell has a limited output in the world due to the extremely high industrial‐production demands for avoiding problems due the occurrence of oxidative side reactions, thermal instability, or extremely high temperatures for the dissolution process and uncontrolled fibrillation with the NMMO solvent.…”
Section: The Dissolution Of Cellulosementioning
confidence: 99%
“…[ 60 ] The active N–O dipoles and the oxygen groups of NMMO can form hydrogen bonds with the anhydrous glucopyranose unit (AGU) of cellulose, leading to the disruption of the cellulose’s intermolecular hydrogen bonds, eventually establishing a strong complex by forming new hydrogen bonds in the homogeneous cellulose solution. [ 58,61 ] The commercialized Lyocell fibers spun from NMMO/H 2 O solution exhibit good mechanical properties up to 5.4 cN dtex −1 . [ 62 ] Nevertheless, Lyocell has a limited output in the world due to the extremely high industrial‐production demands for avoiding problems due the occurrence of oxidative side reactions, thermal instability, or extremely high temperatures for the dissolution process and uncontrolled fibrillation with the NMMO solvent.…”
Section: The Dissolution Of Cellulosementioning
confidence: 99%
“…As an example can be mentioned coordination polymers with symmetric and unsymmetrical ligands-4,4and 2,2 -bipyridine N,N'-dioxides and N-oxides [77]. Recent reports concern also pH-responsive polystyrene-b-poly(4-vinylpyridine-N-oxide) membranes [78] and the possibility of applying the coatings from a solution of cellulose-N-methylmorpholine-N-oxide to paper [79]. In the first case, at low pH the pores open (the solution flow increases), and at high pH, the pores close (the solution flow is reduced).…”
Section: Other Applications Of Pyridine N-oxidesmentioning
confidence: 99%
“…It also affects fire resistance, thermal and electrical conductivity, and the friction coefficient. Paper with a coating from a cellulose-N-oxide solution was characterized above all by higher hydrophobicity and smoothness of the surface as well as better tear resistance [79].…”
Section: Other Applications Of Pyridine N-oxidesmentioning
confidence: 99%
“…With the increasing improvement of dissolution technology, NMMO solvent system has become one of the most promising cellulose solvents. (Krysztof, Olejnik et al, 2018) The preparation technology of NMMO/H 2 O regenerated cellulose has been industrialized (Carrick, Pendergraph et al, 2014) and widely used in cellulose-based aerogels,(C. Zhang, Zhai et al, 2017) hydrogels, (Cao, Li et al, 2018) lms, beads, (Hao, Sh et al, 2020) microspheres, (Sw, Yg et al, 2020) laments, and textile fabrics. (Jie Cai, Liu et al, 2012;Jiang, Wang et al, 2017) Korpela et al(Korpela, Kunnari et al, 2017) found that NMMO could dissolve cellulose to enhance the properties of nano cellulose (CNF) lms.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the CNF membrane with a smooth surface, good water resistance, and high strength were obtained. Marta et al (Krysztof et al, 2018) found a new method to improve paper properties.…”
Section: Introductionmentioning
confidence: 99%